2015
DOI: 10.1111/epi.13266
|View full text |Cite
|
Sign up to set email alerts
|

Towards a clinically informed, data‐driven definition of elderly onset epilepsy

Abstract: SUMMARYObjective: Elderly onset epilepsy represents a distinct subpopulation that has received considerable attention due to the unique features of the disease in this age group. Research into this particular patient group has been limited by a lack of a standardized definition and understanding of the attributes associated with elderly onset epilepsy. Methods: We used a prospective cohort database to examine differences in patients stratified according to age of onset. Linear support vector machine learning i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…We only included studies presenting data specific to elderly individuals. We initially defined elderly as individuals aged at least 65 years as per recent literature but modified our definition to those aged at least 60 years after having identified several studies that used this younger age limit, which is also consistent with the United Nations definition of the elderly . We excluded trials where >20% of individuals were younger than 60 years, unless there were sufficient data regarding individuals older than 60 years to be analyzed separately as a subgroup.…”
Section: Methodsmentioning
confidence: 99%
“…We only included studies presenting data specific to elderly individuals. We initially defined elderly as individuals aged at least 65 years as per recent literature but modified our definition to those aged at least 60 years after having identified several studies that used this younger age limit, which is also consistent with the United Nations definition of the elderly . We excluded trials where >20% of individuals were younger than 60 years, unless there were sufficient data regarding individuals older than 60 years to be analyzed separately as a subgroup.…”
Section: Methodsmentioning
confidence: 99%
“…LOE emerges from the literature as a distinct phenotype of epilepsy. Josephson et al [9]identified key characteristics of LOE, including an absence of learning disorders or mental health issues, higher prevalence of focal seizures, and a lower prevalence of generalised tonic-clonic seizures. Although this phenotype is more common with increasing age, it first emerges in the 30s, with an increasing prevalence in the 40s and peak incidence in 60s and 70s [9].…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Josephson et al [9]identified key characteristics of LOE, including an absence of learning disorders or mental health issues, higher prevalence of focal seizures, and a lower prevalence of generalised tonic-clonic seizures. Although this phenotype is more common with increasing age, it first emerges in the 30s, with an increasing prevalence in the 40s and peak incidence in 60s and 70s [9]. Furthermore, there is evidence that LOE associated J Wall with white matter lesions (WMLs) more frequently exhibits a phenotype of temporal lobe onset; whereas post-stroke seizures are more commonly associated with a frontal lobe focus [10].…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Age is more than just a chronological number and encompasses physiological changes, comorbidities and frailty among other measure. However, we note that an accepted age cut-off for the elderly is required to standardize epilepsy research findings [93].…”
Section: Validity Of Age Cut-offmentioning
confidence: 99%